Impact of Natural Pozzolan and the Degree of Circularity of Aggregates on the Thickness, Strength and Durability of ITZ in Concrete (Modeling and Experimentation) - Lazhar Loumachi; Bouzidi Mezghiche; Ahmed Abderraouf Belkadi (Aceh International Journal of Science and Technology, 2023)
The interfacial transition zone (ITZ) has a significant negative impact on the structural performance of concrete. This negative impact can be ameliorated by introducing mineral additions into the concrete. In this study, different forms (degree of circularity) of coarse aggregates and three contents (10 %, 15 % and 20 %) of mineral addition (natural pozzolan) were used to prepare ordinary concrete. This article aims to determine the optimal and effective mixture (the best form of aggregate and addition). This article aims to determine the optimal and efficient mixture (the best form of aggregate and addition) on the basis of mechanical (compressive strength), and chemical (immersion in 3.5 % H2SO4 solution) tests. Furthermore, the effect of the interaction between the aggregate and the modified cementitious matrix was analyzed and discussed using the scanning electron microscope (SEM). The results show that the effect of the addition of 20 % pozzolana improves the aggregate/matrix transition zone, which made it possible to develop a maximum compressive strength at 60 days (51 MPa). In addition, the effect of mineral additions varies depending on the shape of the coarse aggregate. Thus, an effective numerical modeling of the compressive strength is based on the approach of the full factorial design taking into account the degree of circularity of the coarse aggregates and the content of the pozzolan.